(3cJGH aj Yde GdfLhes - (3GdRhGhj, YHO Gddg Hf YHO Gddg Hf Ydj GdefLe Hf GdeMaha, (B800(3g`s
(3ChdgG (B:s
(3bGd(B...(3YHO Gddg Hf GdeMaha GdefLe(B...(3deG QCjJ cJHG cKjQI hcKjQG ef GdfGS ef SGFQ GdCLfGS eLJgOjf eLJgOjf aj WdH GdcfGjGJ hGdcGFfGJ bHd hbhYgG(B...s
(3BNQgG (B:s
(3hgPg GdYdGeGJ hGdaGJ JXgQ aj GdCQHY GdUhQ GdJj JSei GdCegGJ Ydi GdhdG haj GdCQHY UhQ GdJj JSei GdHfGJ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B256s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3Gdadc hGdJfLje hGdejbGJs